Computation of flows around stationary and rotating cylinders and a tandem of cylinders at near-critical regimes using DDES coupled with a laminar-turbulent transition model - Stabnikov Andrey; Garbaruk Andrey (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
The objective of this paper is to assess the capabilities of a hybrid RANS-LES approach DDES coupled with algebraic RANS turbulence transition models SST KD and SST alg-γ, allowing the prediction of the laminar-turbulent transition (LTT). The approach is applied to calculations of flows around stationary and rotating cylinders as well as a tandem of stationary cylinders. It is shown that for the simulations of the flows under consideration, this approach significantly outperforms the standard SST DDES (within the standard SST DDES it is assumed that the flow is completely turbulent, and the LTT is not taken into account). At the same time, the obtained computational results depend significantly on the choice of the LTT model, and neither of the two models has a clear advantage in terms of agreement between the computational results and experimental data.